2002
DOI: 10.1021/jp012901f
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Hydrolytic Polymerization of Aqueous Zirconium Ions Using the Fluorescent Probe Pyrenecarboxylic Acid

Abstract: We report on the hydrolytic polymerization of zirconium in aqueous solution using the transient optical response of the fluorescent molecule 1-pyrenecarboxlyic acid (PCA) as a probe. We have measured the fluorescence lifetimes and rotational diffusion dynamics of PCA in “aged” aqueous solutions of tetravalent zirconium to understand the ability of fluorescent probes to report on the structural aspects of hydrous metal oxide self-assembly. The degree of polymerization, and therefore the extent of solute organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Moreover, the power-law scattering of SAXS profiles in q -region II provides insight into the difference between these species. The exponent is close to 4 for the black line, according to Porod’s law, implying the formation of colloidal particles. On the other hand, the exponent is 2 for the red and green lines, which is typically observed in planar scatterers, such as [Zr 4 (OH) 8 (H 2 O) 16 ] 8+ (see Figure S3).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, the power-law scattering of SAXS profiles in q -region II provides insight into the difference between these species. The exponent is close to 4 for the black line, according to Porod’s law, implying the formation of colloidal particles. On the other hand, the exponent is 2 for the red and green lines, which is typically observed in planar scatterers, such as [Zr 4 (OH) 8 (H 2 O) 16 ] 8+ (see Figure S3).…”
Section: Discussionmentioning
confidence: 71%
“…The power-law scattering of I nor ( q ) in region II should reflect the interfacial structure of the primary particles. Thus, we examined the scattering profiles in detail at q < 5.0 nm –1 (Figure ) using the Porod plot of ln [ I nor ( q ) q 4 ] versus q 2 . In this q range, ln [ I nor ( q ) q 4 ] satisfies where S is the interfacial area per unit volume, Σ is a parameter characterizing the interfacial width between the solid phase and aqueous solution, and the characteristic interfacial thickness, t , is generally defined as . Porod analysis of the power-law scattering showed that the slope decreased as the aging temperature increased.…”
Section: Discussionmentioning
confidence: 99%
“…The higher Zr 4+ ratio is attributed to both complete surface phosphate coverage and also due to the transfer of other soluble species such as ZrO(OH) y 2−y (including nonstoichiometric water) or hydrous oxide polymers from the trough to surface. 37,38 Phospholipid Langmuir film dynamics minimally affected by metal ion identity. Fluorescence recovery after photobleaching (FRAP) experiments were performed on the film surfaces to better understand the influence of the metal ion identity in the under-layer on the dynamics of the supported DMPC film.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Given the buffered pH of 7.5 and relatively low hydroxide K sp of zinc, the increased Zn 2+ ratio is attributed to the transfer of neutral Zn­(OH) 2 species into the adventitious water layer described earlier. The higher Zr 4+ ratio is attributed to both complete surface phosphate coverage and also due to the transfer of other soluble species such as ZrO­(OH) y 2– y (including nonstoichiometric water) or hydrous oxide polymers from the trough to surface. , …”
Section: Resultsmentioning
confidence: 99%
“…Aqueous solution chemistry of zirconium and hydrolytic polymerization of aqueous zirconium ions are reported in several papers [29][30][31][32][33][34].…”
Section: Effect Of Initial Phmentioning
confidence: 99%